Bilangan 5:11–31: Ritual Sotah sebagai Terobosan Budaya di Timur Tengah Kuno - Yong, Steven (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Numbers 5:11–31: Sotah as a Cultural Breakthrough in the Ancient Near East. Numbers 5:11–31 could be interpreted as a kind of sexism and repression to women. In the Mishnaic tradition, the passages indeed are being understood and developed in such a manner. From tractate Sotah in Mishnah, the suspected adulterous wife indeed is ashamed and treated as a prostitute. This article seeks to present another perspective on the passage. This article uses the sociological study method to identify the sociological problems alleged against the passage based on the explanation of the Sotah tractate in the Mishnah. Afterward, the inferior position of women in the ancient Near East will be explained as a cultural context to understand the passage better. Finally, considering this cultural context and comparing the Sotah ritual with the common rituals in the ancient Near East, this article argues that Numbers 5:11–31 could be seen as a cultural breakthrough to protect women, which are considered marginalized.